Evaluation of dental and basal arch forms using cone-beam CT and 3D virtual models of normal occlusion - Bayome Mohamed; Park Jae Hyun; Han Seong Ho; Baek Seung-Hak; Sameshima Glenn T.; Kook Yoon-Ah (Australasian Orthodontic Journal, 2013)
Objectives: To evaluate the relationship between the mandibular dental and basal arches using CBCT, and to assess the correlation between basal arch dimensions derived from CBCT and 3-dimensional (3D) virtual models in a cohort sample exhibiting normal occlusions.